Studi Eksperimental Laju Perpindahan Panas dan Laju Aliran Massa Fluida Pada Karbon Aktif Bambu Betung Dengan Temperatur 600°C Holding Time 60 Menit - Siregar, Manatap H.Ady; Wijaksana, Hendra; Prananda Surya, I Gede Teddy (Teknik Desain Mekanika, 2021)
Abstract Currently the vapor compression cycle is very dominant although it uses a lot of energy and is less efficient when operating in a hot climate. This energy consumption increases dramatically as the ambient temperature increases. Therefore, a cooling system that is environmentally friendly and more energy efficient is needed. One alternative cooling system is direct evaporative cooling. In a direct evaporative cooling system, the cooling effect is provided by the evaporation process that occurs in the pad material that has been wetted by water. The pad material itself is used for the application of evaporative cooling systems, as a cooling medium. This study uses activated carbon charcoal as a pad material to determine the effect of fluid mass flow rate and heat transfer rate on a direct evaporative cooling system using carbonization temperatures of 400 oC, 500 oC, 600 oC, 700 oC, 800 oC then activated with a temperature of 600 oC holding time 60 minutes. This test includes several tests such as SEM test, contact angle test, and capillarity test. The results of all tests show that the ABB 1 specimen (400 oC) has the highest mass flow rate and heat transfer rate of 23.7 x10-5 Kg/s and 0.53 Watt which can be used as potential for the manufacture of new pad materials in the direct evaporative cooling system. Keywords: Bamboo betun, direct evaporative cooling, carbonization, activation, fluid mass flow rate, heat transfer rate